The synthesis and structural aspects of the perbromo-functionalised thiaboranes closo-SBnBrn (n = 5, 9, 11): the solid-state structure of the octahedral closo-SB5Br5, governed by strong dihalogen contacts - Keller, Willi; Ballmann, Joachim; Fanfrlík, Jindřich; Hnyk, Drahomír (Chemical communications, 2025)
Co-pyrolysis reactions of B2Br4 with S2Br2 at 350 °C in vacuo yielded the brominated thiaboranes closo-SB5Br5 (1), closo-1-SB9Br9 (2) and closo-SB11Br11 (3), confirmed by high-resolution mass spectrometry, experimental and computational 11B NMR spectroscopy. The strong Brδ+(σ-hole)⋯Brδ−(ring) attraction has been the decisive energy contribution in the crystal of 1.
Im Titel ist "n" zweimal tiefgestellt, im Zusatz "5" zweimal tiefgestellt
Gesehen am 18.06.2025